Chromosomal Mapping of Repetitive DNAs in the Grasshopper Abracris flavolineata Reveal Possible Ancestry of the B Chromosome and H3 Histone Spreading - Bueno, Danilo [UNESP]; Palacios-Gimenez, Octavio Manuel [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP] (Public Library of Science (PLoS), 2013)
Supernumerary chromosomes (B chromosomes) occur in approximately 15% of eukaryote species. Although these chromosomes have been extensively studied, knowledge concerning their specific molecular composition is lacking in most cases. The accumulation of repetitive DNAs is one remarkable characteristic of B chromosomes, and the occurrence of distinct types of multigene families, satellite DNAs and some transposable elements have been reported. Here, we describe the organization of repetitive DNAs in the A complement and B chromosome system in the grasshopper species Abracris flavolineata using classical cytogenetic techniques and FISH analysis using probes for five multigene families, telomeric repeats and repetitive C0t-1 DNA fractions. The 18S rRNA and H3 histone multigene families are highly variable and well distributed in A. flavolineata chromosomes, which contrasts with the conservation of U snRNA genes and less variable distribution of 5S rDNA sequences. The H3 histone gene was an extensively distributed with clusters occurring in all chromosomes. Repetitive DNAs were concentrated in C-positive regions, including the pericentromeric region and small chromosomal arms, with some occurrence in C-negative regions, but abundance was low in the B chromosome. Finally, the first demonstration of the U2 snRNA gene in B chromosomes in A. flavolineata may shed light on its possible origin. These results provide new information regarding chromosomal variability for repetitive DNAs in grasshoppers and the specific molecular composition of B chromosomes. © 2013 Bueno et al.
Keywords: DNA fragment; histone H3; repetitive DNA; RNA 18S; RNA 5S; satellite DNA; Abracris flavolineata; animal cell; animal tissue; autosome; bioaccumulation; Caelifera; centromere; chromosome analysis; chromosome map; chromosome variant; DNA sequence; female; fluorescence in situ hybridization; genetic conservation; karyotype; male; nonhuman; nucleotide sequence; plesiomorphy; RNA gene; telomere